ANALYSIS EARLY READING AND WRITING (MMP) ABILITY OF GRADE 1 STUDENTS AT SDN MLATEN 1 - Aqidatul Izza TPP (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
The Early Reading Writing Learning (MMP) is a learning activity for students in lower grades in order to acquire initial reading and writing skills. Early Reading Writing Learning (MMP) is a teaching and learning activity that aims to provide provision for grade 1 students with good reading and writing skills. Early Reading and Writing Learning (MMP) is important for students in the lower grades to master as a basis for further preparation at the next level. This research aims to analyze the Early Reading and Writing Ability for grade 1 students at SDN Mlaten 1. This research is a research using a qualitative research approach. A total of 29 grade 1 students became subjects in this study. This research was conducted in the even semester of the 2022/2023 academic year, starting from February 21 – March 1 2023.This study used several data collection methods, including observation, interviews, tests, and documentation. The early reading and writing ability of grade 1 students at SDN Mlaten 1 is moderate. Out of a total of 29 grade 1 students at SDN Mlaten 1, 8 students had high MMP abilities, 11 students had moderate abilities, and 10 students had low MMP abilities.